A Note for Indonesia’s Border Diplomacy in Tanjung Datu, West Kalimantan - Iva Rachmawati; Machya Astuti Dewi (Jurnal Hubungan Internasional, 2020)
This article aims to propose a fundamental overhaul of the understanding of Indonesia’s border diplomacy, which has so far state-centric and only prioritizes the role of the central government. Despite being in the high politics issue, border diplomacy can no longer elitist practiced. Referring to several problems that arise at the practical and academic level, Indonesia’s border diplomacy is the time to expand diplomacy by considering other important actors, namely subnational actors and non-state actors. Not only at the provincial level, but sub-national actors to the lowest level in the border region also have a significant contribution to Indonesia’s border diplomacy, as well as non-state actors from academia. This article is the result of research based on a qualitative methodology using Personal Communication withs and documentation studies. The research discovered many essential notes, including firstly, the confusion of information in the Tanjung Datu issue in both Camar Bulan and Gosong Niger has harmed the bilateral relations between Indonesia and Malaysia. Second, independence in the practice of relations between two communities between countries showed that subnational actors have a vital influence on Indonesia-Malaysia bilateral relations.